Esomeprazole and apixaban pharmacokinetic interactions in healthy rats - Ali Jaber; Israa Al-Ani; Mohammad Hailat; Enas Daoud; Anmar Abu-Rumman; Zainab Zakaraya; Bashar J.M. Majeed; Osaid Al Meanazel; Wael Abu Dayyih (Heliyon, 2022)
Esomeprazole is used in various clinical settings where a decrease in gastric acid production is desired since it is a proton pump inhibitor. Apixaban, an anticoagulant, is used to reduce the risk of stroke in patients with certain cardiovascular diseases. This research aims to examine the effects of giving esomeprazole and apixaban to rats simultaneously, as well as to measure their pharmacokinetics and look for statistical differences or interactions. A method for the simultaneous determination of esomeprazole and apixaban in rat plasma was developed using HPLC/MS and validated by ICH guidelines. Five groups of Wistar rats were created, and the drugs were administered as follows: esomeprazole (5 mg/kg) intravenously, apixaban (125 mcg/Kg) intravenously, esomeprazole (5 mg/kg) orally, apixaban (250 mcg/kg) orally, and esomeprazole (5 mg/kg) and apixaban (250 mcg/kg) both orally. Both drugs' concentrations were measured in plasma samples collected on a predetermined schedule. The pharmacokinetics of both drugs were calculated and statistically analyzed using a 90% confidence interval and non-compartmental analysis. When the two drugs were combined, apixaban’s Cmax and AUC increased while esomeprazole’s Cmax and AUC decreased. On the other hand, Apixaban’s Tmax decreased with an increase in esomeprazole’s Tmax, indicating a possible interaction between the two drugs. When both drugs were taken together, their bioavailability was reduced, implying that less esomeprazole was absorbed over time.